Associations of 25-hydroxyvitamin D status and vitamin D supplementation use with mortality due to 18 frequent cancer types in the UK Biobank cohort - Sha, Sha; Chen, Li-Ju; Brenner, Hermann; Schöttker, Ben (European journal of cancer, 2023)
Although the associations of serum 25-hydroxyvitamin D (25(OH)D) levels and vitamin D supplementation with total cancer mortality are well-known, evidence regarding the association of 25(OH)D and cancer site-specific mortality is predominantly limited to common cancer types, and most studies on vitamin D supplementation use have limitations on sample size and the adjustment of important confounding factors.
Online veröffentlicht am 17. Juli 2023, Artikelversion vom 5. August 2023
Gesehen am 08.11.2023